Effects of prohexadione calcium applications on growth and yield characteristics of cucumber (Cucumis sativus L.) - Başak, Hakan (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study was conducted to determine the effects of growth regulator prohexadione calcium (Pro-Ca) and inhibitor gibberellic acid on some parameters (yield, pigment levels of leaves, nutrient contents, proline, enzyme activities and fruit quality) when applied at different doses (0, 15, 30, 45, and 60 mg L-1). Chemicals were applied after transplanting seedlings. A total of 12 plots including 3 plants for each dose were used in randomised plot experimental design. Although it has a positive effect on leaf proline content and enzyme activities, 45, and 60 mg L-1 doses of Pro-Ca had negative effects on morphological parameters (excluding stem diameter), yield, leaf pigment (excluding chlorophyll a) and nutrient contents compared to control. High Pro-Ca doses generally affected the fruit quality properties positively while 15 mg L-1 of Pro-Ca did not affect other parameters, except decreasing fruit yield. A 30 mg L-1 of Pro-Ca dose was the most positive effective dose on the examined parameters. The highest vegetative development, yield, nutrient uptake and proline content were obtained from the plants subjected to 30 mg L-1 of Pro-Ca dose. Moreover, this dose increased fruit firmness, TSS, EC values and enzyme activities compared to control. Being an important quality criterion in cucumber storage after harvest, the weight loss rate 29.4% was lower in fruits obtained from the plant having 30 mg L-1 of Pro-Ca dose compared to that of the control plants. Therefore, 30 mg L-1 of Pro-Ca application, beside its positive effects on plant growth, yield and fruit quality, can be suggested for also increase shelf life of fruits in cucumber cultivation in greenhouse.